SIMULATION OF SUBGRADE EMBANKMENT ON WEAK BASE - Petrenko, V. D.; Sviatko, I. O. (Science and Transport Progress, 2015)
Purpose. This article provides: the question of the sustainability of the subgrade on a weak base is considered in the paper. It is proposed to use the method of jet grouting. Investigation of the possibility of a weak base has an effect on the overall deformation of the subgrade; the identification and optimization of the parameters of subgrade based on studies using numerical simulation. Methodology. The theoretical studies of the stress-strain state of the base and subgrade embankment by modeling in the software package LIRA have been conducted to achieve this goal. Findings. After making the necessary calculations perform building fields of a subsidence, borders cramped thickness, bed’s coefficients of Pasternak and Winkler. The diagrams construction of vertical stress performs at any point of load application. Also, using the software system may perform peer review subsidence, rolls railroad tracks in natural and consolidated basis. Originality. For weak soils is the most appropriate nonlinear model of the base with the existing areas of both elastic and limit equilibrium, mixed problem of the theory of elasticity and plasticity. Practical value. By increasing the load on the weak base as a result of the second track construction, adds embankment or increasing axial load when changing the rolling stock process of sedimentation and consolidation may continue again. Therefore, one of the feasible and promising options for the design and reconstruction of embankments on weak bases is to strengthen the bases with the help of jet grouting. With the expansion of the railway infrastructure, increasing speed and weight of the rolling stock is necessary to ensure the stability of the subgrade on weak bases. LIRA software package allows you to perform all the necessary calculations for the selection of a proper way of strengthening weak bases.